Janice Vancleave's ecology for every kid : easy activities that make learning science fun. - VanCleave, Janice Pratt (New York : Wiley, 1996)
Experiments and activities, using everyday materials, designed to teach facts, concepts, and problem solving strategies for helping the environment.
Includes index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
7.5.
7.5
Keywords: Ecology -- Experiments -- Juvenile literature; Ecology -- Experiments; Habitat (Ecology); Science -- Experiments; Ecology -- Experiments; Habitat (Ecology); Science -- Experiments